Pemahaman Keigo Oleh Mahasiswa Pendidikan Bahasa Jepang Universitas Riau angkatan 2019 - Rohmadany, Syeren (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2022)
Japan is a nation that pays great attention to politeness, especially when speaking. This can be seen from the special form in expressing politeness and respect. In Japanese it is termed keigo. Keigo is a variety of respectful language used in Japanese and is one of the characteristics of the Japanese language. In general, keigo is divided into three types, namely sonkeigo, kenjougo, and teineigo. This study discusses the comprehension of keigo in terms of function, meaning, and form in class 2019 students of the Japanese Language Education Study Program, FKIP University of Riau. The purpose of this study was to find out how the understanding of keigo in class 2019 students was. The method used in this study was descriptive quantitative. The results of this study indicate that the students' understanding of the class of 2019 towards keigo as a whole is in the low category, apart from the lack of student understanding of keigo, the period of time from receiving material about keigo with the research time is quite far so it can be concluded that students have limitations in remembering the material.